PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN KEPANDUAN DIVISI PANDU BANDAR UTAMA PADA PT. IPC PELABUHAN INDONESIA II (Cabang Tanjung Priok) - Ade Nugraha Saputra; Agus Hermani; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2012)
Motivation and discipline to work for the achievement of a factor supporting high performance in order to achieve optimal company profit. If the motivation and discipline work still god, then a company employee performance can be achieved, which is high and vice versa. Formulation of the problem in this research is still there is wastage of time of work, on the other hand the compensation given is already high enough and work rules are obvious. This research aimed to determine the extent of the influence of motivation and discipline work against employee performance parts production. The type of research that is used is explanatory research. The data base collection by using a questionnaire which was distributed to 34 respondents from the Port Employee of Scouting Division Chief at the PT. IPC Pelabuhan Indonesia II (Branch Tanjung Priok). Data analyzed qualitatively without numbers and quantitative analysis using the validity test, reliability test, simple linier regression, T-test, double linier regression, F-test, with the help of the program SPSS. The conclusion is working motivation performance of work and discipline employees have been good. The result analysis proving that partial method how major motivation to work performance by employees 53.9%, the work of discipline 53.9%. The simultaneously how major motivation to work and discipline work performance by employees 61.3%. The suggestions can be submitted is in terms of the motivation of working to foster awareness of the importance of interpersonal relationships that employees not only in terms of the level of employment, the influential achievements ever increasing bonuses received. Then in terms of need for acceleration of work discipline work procedures or standard working time so that it can increase the intensity of the coordination work and not give an opportunity to excess employees to do other activities during work hours.